Regional transarterial chemoembolization combined with chemoradiotherapy for locally advanced rectal cancer: a retrospective study of a new combination - Meng, Wen-Jun; Liu, Chun-Hua; Zheng, Ru-Jun; Li, Chun-Xue (Frontiers in Oncology, 2023)
Abstract Objectives: Locally advanced rectal cancer (LARC) has a high risk of distant metastasis (DM). Currently, many treatment courses of LARC have been arisen, but patients’ DM status has not been significantly improved. This study was designed to compare the effect between preoperative regional transarterial chemoembolization combined with neoadjuvant chemoradiotherapy and standard neoadjuvant therapy on preventing DM in patients with LARC. Methods: A total of eighty-one LARC patients between July 2013 and May 2018 were enrolled in this retrospective study. Among them, forty-four patients received preoperative regional transarterial chemoembolization combined with concurrent chemoradiotherapy (the interventional group), and thirty-seven patients received only neoadjuvant chemoradiotherapy (the control group). The baseline data, preoperative toxicities, postoperative DM rate within one, two, and three years, and postoperative complications, were compared between the two groups. Results: All patients successfully completed their treatments. There were no significant differences between the two groups in age, gender, tumor size, distance between the tumor and anal verge, CEA level, lymphovascular invasion, or tumor stage before treatment. The pathological T staging post-treatment in the interventional group was significantly reduced compared to that of the control group (p =0.025). There were no significant differences between groups in DM rates within one and two years after surgery. In terms of DM rate within three years after surgery, the interventional group was significantly lower than that of the control group (9.1 % vs. 29.7 %, p=0.036). Conclusion: Preoperative regional transarterial chemoembolization combined with concurrent chemoradiotherapy may play an important role in reducing postoperative DM in LARC.